MICROBIOLOGICAL TRACES OF ANCIENT FOOD IN VESSELS FROM BURIALS - Kasirskaa, Natal'a Nikolaevna; Cernyseva, Elena Vladislavovna; Homutova, Tat'ana Eduardovna; Evstigneev, Aleksej Maksimovic; Klesenko, Aleksandr Aleksandrovic; Malasev, Vladimir Ur'evic; Mimohod, Roman Alekseevic; Zenuk, Dmitrij Igorevic; Amaakan, Simon Gevorgovic; Bobohan, Arsen Aleksandrovic; Vladimirovic, Aleksandr Borisov (History, Archeology and Ethnography of the Caucasus, 2026)
The objective of this study was to introduce new data regarding the trophic structure and taxonomic identification of microorganisms preserved in the bottom sediment of ritual vessels. Samples were collected from various regions across the Caucasus, the steppe zones of Russia, and Armenia. Soil samples from 42 vessels were analyzed. Based on the quantitative assessment of trophic microbial groups, it was determined that 4 samples contained no food remains, 16 samples contained low-calorie food, and 12 samples contained food with high-fat content. In 16 of these samples – half of which belonged to the high-fat group – the taxonomic classification of food-related bacteria was conducted for the first time using 16S rRNA gene sequencing. Additionally, yeast strains were identified through ITS1–5.8S–ITS2–28S rRNA gene sequencing. The study identified lactic acid fermentation bacteria, specifically Sporolactobacillus terrae, Sporolactobacillus vineae, Heyndrickxia coagulans, and Heyndrickxia acidiproducens, as well as the yeast Candida sorbosivorans. Pathogenic bacteria, including Bacillus licheniformis and Clostridium botulinum, were also detected. The presence of Clostridium botulinum was verified via luminescence microscopy of cell consortia isolated from the soil. Furthermore, the phylogenetic position of the Sporolactobacillus vineae strain, previously isolated from the sediment of an ancient oinochoe, was refined. Taxonomic diagnostics of microorganisms in the soil of ritual vessels is essential for assessing and monitoring microbial communities within burial complexes. In these contexts, the interment of food products contributed to increased microbial diversity and facilitated the preservation of ancient, biotechnologically significant strains.
Keywords: Caucasus; Crimea; burials; vessels; food; lipolytic microorganisms; lactic acid bacteria